The Terms of Trade and Economic Fluctuations - Mendoza, Enrique (IMF Working Papers; Working Paper ;, 1992)
A three-good, stochastic intertemporal equilibrium model of a small open economy is used to examine the link between terms of trade and business cycles. Equilibrium co-movements of model economies representing industrial and developing countries are computed and compared with the stylized facts of 30 countries. The results show that terms-of-trade shocks account for half of observed output variability and that the model mimics the Harberger-Laursen-Metzler effect and produces large deviations from purchasing power parity. The elasticity of substitution between tradable and nontradable goods and the persistence of the shocks play a key role in producing these results.